Highly Active Fe-N/C Oxygen Electrocatalysts Based on Silicon Carbide Derived Carbon. (8th September 2020) - Teppor, Patrick; Jäger, Rutha; Hints, Johanna; Volobujeva, Olga; Valk, Peeter; Koppel, Miriam; Lust, Enn
Abstract : In this work oxygen reduction catalysts were synthesized by modifying silicon carbide derived carbon with Fe and N through ball milling. The presence of a process control agent and grinding ball diameter in the milling step were varied in order to study their effect on both the physical and electrochemical characteristics of the catalysts prepared. It was established that the ball diameter and process control agent can noticeably impact the surface morphology, particle size distribution, and specific surface area of the materials. Despite these differences, similar high half-wave potential values of 0.85 V vs RHE in alkaline media were established for all the catalysts. However, the electrochemical performance of the materials varied considerably in a PEMFC experiment. More specifically, particle size distribution and specific surface area appear to be important parameters when studying non-platinum group metal catalysts in single cell setups.